The Micro Hand S vs. da Vinci Surgical Robot-Assisted Surgery on Total Mesorectal Excision: Short-Term Outcomes Using Propensity Score Matching Analysis - Zeng, Yijia; Wang, Guohui; Li, Zheng; Lin, Hao; Zhu, Shaihong; Yi, Bo (Frontiers in Surgery, 2021)
Objective To compare the operation mode and clinical short-term outcomes of the Micro Hand S and the da Vinci surgical robot, we chose total mesorectal excision (TME) as the standard procedure for its good reflection of robot-assisted surgery advantages. Methods We collected a total of 54 consecutive patients who underwent robot-assisted TME by two surgical robots from January 2016 to October 2020. We used propensity score matching (PSM) to create balanced cohorts of Micro Hand S group (n = 14) and da Vinci group (n = 14). Robotic installation and operation time, hospital and surgery costs, and intraoperative and postoperative clinical outcomes were compared. Results In terms of robotic installation time, the Micro Hand S robot took longer than the da Vinci robot (24.2 ± 9.4 min vs. 17.1 ± 5.1 min, P < 0.05). As for the costs, the Micro Hand S group had lower total hospital costs (87040.1 ± 24676.9 yuan vs. 125292.3 ± 17706.7 yuan, P < 0.05) and surgery costs (25772.3 ± 4117.0 yuan vs. 46940.9 ± 10199.7 yuan, P < 0.05) than the da Vinci group. There were no statistically significant differences (P > 0.05) in other indicators, including total operation time, robotic operation time, blood loss, time to first liquid diet, time of getting out of bed, and hospital stay. Conclusion The Micro Hand S enables patients with rectal cancer to enjoy lower medical costs of robotic surgery.